A comparative study on NPV and IRR method: which one is more applicable in decision making / Ahmad Zaki Mahmood - Mahmood, Ahmad Zaki (1993)
I had chosed the topic on the decision making process, especially in the capital budgeting because I had been attracted to the argument of using either Net Present Value(NPV) or Internal Rate of Return(IRR) method in capital budgeting decision making. It had been argued that NPV is superior to that of IRR method but according to the study and research conducted, the number of firms using either one of both method are almost equal. There should be pros and contras supporting the use of the selected method.